Determination of compounds with varied volatilities from aqueous samples using a polymeric ionic liquid sorbent coating by direct immersion-headspace solid-phase microextraction. Issue 20 (11th May 2016) - Merib, Josias; Yu, Honglian; Carasek, Eduardo; Anderson, Jared L.
Abstract : The use of highly robust polymeric ionic liquid (PIL) sorbent coatings combined with direct immersion (DI) and headspace (HS) modes in a single solid-phase microextraction (SPME) procedure coupled to gas chromatography (GC) is reported. Abstract : The use of highly robust polymeric ionic liquid (PIL) sorbent coatings combined with direct immersion (DI) and headspace (HS) modes in a single solid-phase microextraction (SPME) procedure coupled to gas chromatography (GC) is reported. Target analytes with a wide range of volatilities including polycyclic aromatic hydrocarbons, organochlorine pesticides, and phthalate esters were studied. Three PIL-based sorbent coatings were evaluated and the highest extraction efficiency for most analytes was obtained using the PIL coating consisting of the 1-vinylbenzyl-3-hexadecylimidazolium bis[(trifluoromethyl)sulfonyl]imide [VBC16 IM][NTf2 ] IL monomer and the [(VBIM)2 C12 ]2[NTf2 ] IL crosslinker. The combined DI-HS mode allowed for a compromise extraction condition among the different classes of analytes compared to the use of DI and HS modes separately. An extraction temperature of 40 °C and an extraction time of 50 min with 50% of this time in HS mode was optimized by application of a central composite design. Satisfactory analytical performance was achieved with limits of detection varying from 0.003 to 0.15 μg L −1 and calibration curve correlation coefficients ranging from 0.980 to 0.999. Analyte relative recoveries from tap and lake water ranged from 52.3 to 116.8% with relative standard deviations ranging from 0.3 to 19.3%.